Earthquake early warning for southern Iberia: A P wave threshold‐based approach. Issue 17 (6th September 2013) - Carranza, M.; Buforn, E.; Colombelli, S.; Zollo, A.
<x xml:space="preserve">Abstract</x> [1] The south of the Iberian Peninsula is a region in which large, damaging earthquakes occur separated by long time intervals. An example was the great 1755 Lisbon earthquake (intensity Imax = X) which occurred SW of San Vicente Cape (SW Iberian Peninsula). Due to this risk of damaging earthquakes, the implementation of Earthquake Early Warning System (EEWS) technologies is of considerable interest. With the aim of investigating the feasibility of an EEWS in this region of the Iberian Peninsula, empirical scaling relationships have been derived between the early warning parameters and the earthquake size and/or its potential damaging effects for this region. An appropriate and suitable strategy is proposed for an EEWS in the SW Iberian Peninsula, which takes into account the limitations of the existing seismological networks.